Diffraction and vector meson production at HERA - Kapishin, Mikhail (Array, 2008)
Summary: Results of new measurements of diffractive cross sections in deep-inelastic scattering (DIS) and photo-production at HERA are presented. The cross sections of dijet and open charm production are compared with next-to-leading order (NLO) QCD predictions based on parton distribution functions obtained from diffractive inclusive DIS data. A combined NLO QCD fit to the inclusive and dijet DIS data is performed to determine diffractive quark singlet and gluon densities with a better precision. Recent measurements of elastic vector meson production and deeply virtual Compton scattering at HERA are also reviewed